Bulk insulating topological insulator single crystals with ultrahigh electron mobility and methods of making the same

CN117166061BActive Publication Date: 2026-10-16BEIJING INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310975814.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2026-10-16
Estimated Expiration
2043-08-04

AI Technical Summary

Technical Problem

但是,BiSbTeSe2材料中仍然存在BiTe反位(即Bi原子占据Te位置),影响了其体绝缘特性的提高

Benefits of technology

本发明提供了一种具有超高电子迁移率的体绝缘拓扑绝缘体单晶,微量的Sn掺杂可以极大的降低体系中的BiTe反位缺陷,采用微量Sn替换BiSbTeSe2材料中的Bi位,可降低体态的载流子浓度,显著提高单晶材料表面态电子迁移率和体绝缘特性;并且Sn的掺杂量控制是影响单晶材料表面态电子迁移率和体绝缘特性的关键,所述单晶Sn和Bi的摩尔比为(0.01~0.05):(0.95~0.99),替代Bi位的Sn量过高会导致材料中引入额外的Sn杂质,从而导致载流子浓度过高,影响所述单晶材料表面态电子迁移率和体绝缘特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117166061B_ABST
    Figure CN117166061B_ABST
Patent Text Reader

Abstract

The application relates to a bulk-insulating topological insulator single crystal with ultrahigh electron mobility and a preparation method thereof, and belongs to the technical field of single crystal materials. The chemical general formula of the single crystal is Sn x Bi 1‑ x SbTeSe2, wherein 0.01<=x<=0.05. The topological insulator single crystal is prepared by a two-step method, that is, a Sn x Bi 1‑ x SbTeSe2 precursor is obtained by a melting method, and then a single crystal is prepared by a vertical Bridgman method. A trace amount of Sn doping can greatly reduce BiTe antisite defects in the system, the Bi site in the BiSbTeSe2 material is replaced by a trace amount of Sn, the bulk carrier concentration is reduced, and the surface state electron mobility and bulk insulation characteristics of the single crystal material are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a bulk insulating topological insulator single crystal with ultra-high electron mobility and its preparation method, belonging to the field of single crystal material technology. Background Technology

[0002] Topological insulators are internally insulating materials with power-free conductive channels on their surfaces. These surface states are protected by time-reversal symmetry, and their properties are unaffected by impurity scattering. Therefore, topological insulators are considered to have great application potential in low-power electron transport, spintronics, photoelectric detection, and quantum sensing. Bismuth selenide (Bi₂Se₃) family, as large-bandgap three-dimensional topological insulators, is widely used in information and sensor devices due to its stability in air. However, further research has revealed that the bulk insulation properties of Bi₂Se₃ are not ideal, mainly due to quality issues in its single-crystal materials, such as defects and antisites. Therefore, reducing defects and antisites in the material system and improving its bulk insulation properties is crucial. Only by obtaining bulk insulating samples with high surface state electron mobility can we promote subsequent quantum devices and future applications based on topological insulators.

[0003] BiSbTeSe2 (BSTS) has the same crystal structure as Bi2Se3 and is a topological insulator with good bulk insulation properties. Current literature reports the preparation of BiSbTeSe2 single crystals using methods such as the melt growth method and the Bridgman method, and the study and control of their bulk insulation properties. Specifically: 1. Melt Growth Method: BSTS single crystal samples are prepared by melt growth in a muffle furnace. First, the stoichiometric material is placed in a quartz tube. Then, the quartz tube is placed in the center of the muffle furnace, and the temperature is slowly increased to 850°C at a heating rate of 0.1°C / min, and maintained at this temperature for 48 hours, during which the quartz tube is gently shaken for mixing. Finally, the sample is cooled to 550°C at a rate of 0.1°C / min, annealed at this temperature for 96 hours, and then cooled to room temperature at a rate of 0.1°C / min. 2. Bridgman Method: Bridgman growth is carried out in a vertical Bridgman furnace with three coil heaters. One end of the quartz tube prepared according to method 1 is fixed with a thin rope and placed vertically above the first heating zone. The other end of the rope is connected to the motion controller. The temperature zones are set to 670℃ and 770℃ for the warm zone, and 500℃ for the hot zone and cold zone, with the heaters arranged from top to bottom. The quartz tube moves vertically downwards through the furnace at a rate of 0.6 cm / day. 3. Two-step method: The sample grown by method 1 is used as the raw material for method 2.

[0004] Although previous work has reported that BiSbTeSe2 single crystals prepared using existing technologies can achieve a bulk insulation performance of 2 Ωcm at 2 K and a bulk carrier concentration of 10⁻⁶, 15 cm -3 The order of magnitude is sufficient for general quantum device research. However, BiSbTeSe2 materials still have BiTe antisites (i.e., Bi atoms occupying Te sites), which affects the improvement of their bulk insulation properties. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a bulk insulating topological insulator single crystal with ultra-high electron mobility and its preparation method. The insulating properties of BiSbTeSe2 single crystal are improved by doping with Sn, achieving a resistivity close to 10 Ω·m at 2 K, and the bulk carrier concentration is controlled to 10... 13 cm -3 The mobility has increased to 10,000 cm⁻¹. 2 / V s.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows.

[0007] A bulk insulating topological insulator single crystal with ultra-high electron mobility, the single crystal having the general chemical formula Sn. x Bi 1-x SbTeSe2, where 0.01≤x≤0.05.

[0008] Preferably, 0.02≤x≤0.04.

[0009] The present invention discloses a method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility, the method comprising the following steps: (1) The oxide layer on the surface of Sn particles, Bi particles, Sb particles, Te particles and Se particles is removed by hydrogen reduction method; (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn, Bi, Sb, Te and Se in step (1) to remove the oxide layer on the surface in a glove box with water and oxygen content less than 0.1 ppm and filled with argon gas. Place the weighed raw materials in a quartz tube with a conical bottom and vacuum seal the quartz tube. (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, heat it to 850℃~900℃, keep it at a constant temperature for 48h~72h and shake it, then cool it down to 500℃~550℃, keep it at a constant temperature for more than 24h, and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgeman furnace. Set the temperature of the central area of ​​the Bridgeman furnace to 750℃~720℃. The conical bottom of the quartz tube containing the precursor descends through the central area of ​​the Bridgeman furnace at a speed of 0.5mm / h~2mm / h until the bottom of the furnace. Then close the Bridgeman furnace. (5) Open the quartz tube, take out the crystal, and obtain a bulk insulating topological insulator single crystal with ultra-high electron mobility.

[0010] Preferably, in step (1), Sn particles, Bi particles, Sb particles, Te particles and Se particles are respectively loaded into a quartz tube, and then purged with argon in a vacuum sealing system. Finally, hydrogen gas at a pressure of more than 0.8 atmospheres is introduced into the quartz tube to seal the hydrogen gas inside the quartz tube. The above raw materials are annealed at a temperature 50°C below their respective melting points to remove the oxide layer on the surface. After annealing, a diamond cutter is used to cut a groove around the sealed quartz tube. The sealed quartz tube is then broken open in a glove box filled with argon gas and containing less than 0.1 ppm of water and oxygen to obtain raw materials Sn, Bi, Sb, Te and Se with the oxide layer removed.

[0011] Preferably, in step (2), the quartz tube is placed under a vacuum of less than or equal to 5 × 10⁻⁶. -4 The Pa sealing system is sealed.

[0012] Preferably, in step (3), the quartz tube after vacuum sealing in step (2) is placed in a high-temperature furnace and heated to 850℃~900℃ for 11h~12h, kept at a constant temperature for 48h~72h and shaken 30~40 times. The more times it is shaken, the higher the uniformity of the melt. Then, it is cooled to 500℃~550℃ at a rate of 3℃ / h~5℃ / h and kept at that temperature for more than 24h. After that, the high-temperature furnace is turned off to obtain the precursor.

[0013] Beneficial effects This invention provides a bulk insulating topological insulator single crystal with ultra-high electron mobility. A trace amount of Sn doping can significantly reduce BiTe antisite defects in the system. Replacing Bi sites in BiSbTeSe2 material with trace amounts of Sn can reduce the bulk carrier concentration and significantly improve the surface state electron mobility and bulk insulation properties of the single crystal material. Furthermore, controlling the amount of Sn doping is crucial to the surface state electron mobility and bulk insulation properties of the single crystal material. The molar ratio of Sn to Bi in the single crystal is (0.01~0.05):(0.95~0.99). Excessive Sn substitution at Bi sites will introduce additional Sn impurities into the material, resulting in an excessively high carrier concentration, which will affect the surface state electron mobility and bulk insulation properties of the single crystal material.

[0014] This invention provides a method for preparing a bulk insulator topological insulator single crystal with ultra-high electron mobility. The method utilizes hydrogen reduction to remove the naturally formed oxide layer on the surface of the raw material, thereby significantly reducing the defect and impurity content in the prepared single crystal, minimizing the bulk carrier concentration, and improving the carrier mobility. The topological insulator single crystal prepared by this method has great application potential in low-power devices, spintronics, quantum sensing, photoelectric detection, and other fields.

[0015] This invention provides a method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility. The method employs a two-step process to prepare the topological insulator single crystal, firstly by obtaining Sn using a melting method. x Bi 1-x SbTeSe2 precursor was used to prepare single crystal samples using the vertical Bridgman method. By repeatedly shaking the melt in the molten state during the precursor preparation process, the molten precursor was made uniform, thus ensuring that the prepared single crystal samples had uniform phase formation and significantly improving the quality of the topological insulator single crystal.

[0016] This invention provides a method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility. If the raw material is not treated with an oxide layer, the performance of the single crystal will be greatly affected, resulting in insufficient bulk insulation and low mobility. Furthermore, the selection of the crystal growth temperature is crucial, especially in the second step of re-growing the crystal using the Bridgman process. Improper control can lead to the crystal exhibiting metallic properties instead of the desired insulating properties. Attached Figure Description

[0017] Figure 1 The images are photographs of the single crystals prepared in Examples 1-3; (a) is Example 1, (b) is Example 2, and (c) is Example 3.

[0018] Figure 2 The image shows the X-ray diffraction (XRD) pattern of the single crystal prepared in Example 1.

[0019] Figure 3 The image shows a scanning electron microscope (SEM) image (a) and the corresponding energy dispersive spectroscopy (EDS) spectrum (b) of the single crystal prepared in Example 1.

[0020] Figure 4 The image shows the X-ray diffraction (XRD) pattern of the single crystal prepared in Example 2.

[0021] Figure 5 The image shows a scanning electron microscope (SEM) image (a) and the corresponding energy dispersive spectroscopy (EDS) spectrum (b) of the single crystal prepared in Example 2.

[0022] Figure 6The image shows the X-ray diffraction (XRD) pattern of the single crystal prepared in Example 3.

[0023] Figure 7 The image shows a scanning electron microscope (SEM) image (a) and the corresponding energy dispersive spectroscopy (EDS) spectrum (b) of the single crystal prepared in Example 3.

[0024] Figure 8-9 The image shows the electrical properties of the single crystal prepared in Example 1.

[0025] Figure 10 The image shows the electrical properties of the single crystal prepared in Example 2.

[0026] Figure 11 The image shows the electrical properties of the single crystal prepared in Example 3. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to specific embodiments.

[0028] Example 1 A bulk insulating topological insulator single crystal with ultra-high electron mobility, the single crystal having the chemical formula Sn. 0.02 Bi 0.98 SbTeSe2. A method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in this embodiment, the method comprising the following steps: (1) Weigh 5g of Sn particles with a purity of 99.99%, 5g of Bi particles with a purity of 99.999%, 5g of Sb particles with a purity of 99.9999%, 5g of Te particles with a purity of 99.9999%, and 5g of Se particles with a purity of 99.999%. Put the above raw materials into quartz tubes respectively, and then use argon gas to purge them in a vacuum tube sealing system. Finally, fill the quartz tube with hydrogen gas at a pressure of 0.8 atmospheres and seal the hydrogen gas inside the quartz tube. Anneal the above raw materials at a temperature 50°C lower than their respective melting points to remove the oxide layer on the surface. After annealing, use a diamond cutter to cut a groove around the sealed quartz tube. In an argon-filled glove box (the water and oxygen content in the glove box is less than 0.1 ppm), break open the sealed quartz tube to obtain the raw materials with the oxide layer removed from the surface, which are used for the subsequent crystal preparation. (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn 0.0386g, Bi 3.3331g, Sb 1.9815g, Te 2.0767g and Se 2.5701g in a glove box filled with argon gas and containing water and oxygen content less than 0.1ppm using an electronic balance. The weighing error of each raw material is 0.01%. Place the weighed raw materials in a quartz tube with a conical bottom and place the quartz tube in a vacuum of 5×10 -4 The Pa sealing system is sealed; (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, raise the temperature to 850°C after 10 hours, keep it at 850°C for 48 hours and shake it 30 times, then lower the temperature to 550°C at a rate of 3°C / h, keep it at the temperature for 24 hours and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgman furnace. Set the temperature of the central area of ​​the Bridgman furnace to 900°C. The conical bottom of the quartz tube containing the raw material descends through the central area of ​​the Bridgman furnace at a speed of 1 mm / h until it reaches the bottom of the furnace. Then close the Bridgman furnace. (5) Open the quartz tube, take out the crystal and cut it with a wire cutter to obtain single crystal Sn. 0.02 Bi 0.98 SbTeSe2.

[0029] according to Figure 1 (a) As shown in the photograph, the single crystal prepared in Example 1 is bright and free of impurities. XRD characterization of the single crystal prepared in Example 1 yielded the following results: Figure 2 As shown, a comparison with the standard card (ICSD number: 98-016-5226) reveals that all spectral peaks of the single crystal are close to those of Bi₂Se₃ single crystal diffraction peaks, indicating that the prepared single crystal sample and Bi₂Se₃ have similar crystal structures. The elemental content of the single crystal described in Example 1 was analyzed using EDS spectra, and the results are as follows... Figure 3 As shown, characteristic peaks for Bi, Sb, Te, and Se appear, with the elemental composition ratio approaching 1:1:1:2. Since the nominal content of Sn is relatively low, its characteristic peaks cannot be observed in the EDS spectrum. However, the doping of Sn can be indirectly indicated by comparing the resistivity and mobility of doped and undoped samples. Furthermore, the EDS results between different selected regions show very little difference, indicating excellent crystal homogeneity.

[0030] The electrical properties of the single crystal prepared in Example 1 were tested at a temperature of T = 1.7 K, and the results are as follows. Figure 8 and Figure 9 As shown, through electrical transport measurements and using a two-band fitting (which was subsequently used for other samples), the surface state electron mobility of the material was found to be as high as 10000 cm⁻¹.2 / Vs, while the quantum Hall effect is observed on the device ( Figure 9 This represents the highest international record for single-crystal electron mobility in this system, indicating high crystal quality. The resistivity can reach 10 Ωcm at low temperatures. Figure 8 As shown, bulk carriers can be calculated using Hall data, and their values ​​are in the range of 10. 13 cm -3 It is two orders of magnitude lower than the undoped sample.

[0031] Example 2 A bulk insulating topological insulator single crystal with ultra-high electron mobility, the single crystal having the chemical formula Sn. 0.04 Bi 0.95 SbTeSe2. A method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in this embodiment, the method comprising the following steps: (1) Weigh 5g of Sn particles with a purity of 99.99%, 5g of Bi particles with a purity of 99.999%, 5g of Sb particles with a purity of 99.9999%, 5g of Te particles with a purity of 99.9999%, and 5g of Se particles with a purity of 99.999%. Put the above raw materials into quartz tubes respectively, and then use argon gas to purge them in a vacuum tube sealing system. Finally, fill the quartz tube with hydrogen gas at a pressure of 0.8 atmospheres and seal the hydrogen gas inside the quartz tube. Anneal the above raw materials at a temperature 50°C lower than their respective melting points to remove the oxide layer on the surface. After annealing, use a diamond cutter to cut a groove around the sealed quartz tube. In an argon-filled glove box (the water and oxygen content in the glove box is less than 0.1 ppm), break open the sealed quartz tube to obtain the raw materials with the oxide layer removed from the surface, which are used for the subsequent crystal preparation. (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn 0.0775g, Bi 3.2454g, Sb 1.9902g, Te 2.0859g and Se 2.5815g in a glove box filled with argon gas and containing water and oxygen content less than 0.1ppm using an electronic balance. The weighing error of each raw material is 0.01%. Place the weighed raw materials in a quartz tube with a conical bottom and place the quartz tube in a vacuum of 5×10 -4 The Pa sealing system is sealed; (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, heat it to 900°C after 10 hours, keep it at 900°C for 48 hours and shake it 30 times, then cool it down to 550°C at a rate of 3°C / h, keep it at the temperature for 24 hours and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgman furnace. Set the temperature of the central area of ​​the Bridgman furnace to 900°C. The conical bottom of the quartz tube containing the raw material descends through the central area of ​​the Bridgman furnace at a speed of 1 mm / h until it reaches the bottom of the furnace. Then close the Bridgman furnace. (5) Open the quartz tube, take out the crystal and cut it with a wire cutter to obtain single crystal Sn. 0.04 Bi 0.95 SbTeSe2.

[0032] according to Figure 1 (b) As shown in the photograph, the single crystal prepared in Example 2 is bright and free of impurities. XRD characterization of the single crystal prepared in Example 2 yielded the following results: Figure 4 As shown, a comparison with the standard card (ICSD number: 98-016-5226) reveals that all spectral peaks of the single crystal are close to those of Bi₂Se₃ single crystal diffraction peaks, indicating that the prepared single crystal sample and Bi₂Se₃ have similar crystal structures. The elemental content of the single crystal described in Example 2 was analyzed using EDS spectra, and the results are as follows... Figure 5 As shown, characteristic peaks for Bi, Sb, Te, and Se appear, with the elemental composition ratio approaching 1:1:1:2. Due to the relatively low nominal Sn content, no characteristic Sn peaks are observed in the EDS spectrum. However, the presence of Sn can be indirectly indicated by comparing the resistivity and mobility of doped and undoped samples. Furthermore, the EDS results between different selected regions show minimal difference, indicating excellent crystal homogeneity.

[0033] The electrical properties of the single crystal prepared in Example 2 were tested at a temperature of T=2K, and the results are as follows. Figure 10 As shown, the surface state electron mobility of the material is as high as 4200 cm⁻¹, obtained through electrical transport measurements. 2 / Vs, the ultra-high electron mobility indicates high crystal quality.

[0034] Example 3 A bulk insulating single crystal with ultra-high electron mobility, the single crystal having the chemical formula Sn. 0.03 Bi 0.98 SbTeSe2.

[0035] A method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in this embodiment, the method comprising the following steps: (1) Weigh 5g of Sn particles with a purity of 99.99%, 5g of Bi particles with a purity of 99.999%, 5g of Sb particles with a purity of 99.9999%, 5g of Te particles with a purity of 99.9999%, and 5g of Se particles with a purity of 99.999%. Put the above raw materials into quartz tubes respectively, and then use argon gas to purge them in a vacuum tube sealing system. Finally, fill the quartz tube with hydrogen gas at a pressure of 0.8 atmospheres and seal the hydrogen gas inside the quartz tube. Anneal the above raw materials at a temperature 50°C lower than their respective melting points to remove the oxide layer on the surface. After annealing, use a diamond cutter to cut a groove around the sealed quartz tube. In an argon-filled glove box (the water and oxygen content in the glove box is less than 0.1 ppm), break open the sealed quartz tube to obtain the raw materials with the oxide layer removed from the surface, which are used for the subsequent crystal preparation. (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn 0.0435g, Bi 3.3331g, Sb 1.9815g, Te 2.0767g and Se 2.5701g in a glove box filled with argon gas and containing water and oxygen content less than 0.1ppm using an electronic balance. The weighing error of each raw material is 0.01%. Place the weighed raw materials in a quartz tube with a conical bottom and place the quartz tube in a vacuum of 2×10 -4 The Pa sealing system is sealed; (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, raise the temperature to 900°C after 10 hours, keep it at 900°C for 72 hours and shake it 40 times, then lower the temperature to 500°C at a rate of 5°C / h, keep it at the temperature for 24 hours and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgeman furnace. Set the temperature of the central area of ​​the Bridgeman furnace to 950°C. The conical bottom of the quartz tube containing the raw material descends through the central area of ​​the Bridgeman furnace at a speed of 2 mm / h until it reaches the bottom of the furnace. Then close the Bridgeman furnace. (5) Open the quartz tube, take out the crystal and cut it with a wire cutter to obtain single crystal Sn. 0.03 Bi 0.98 SbTeSe2.

[0036] according to Figure 1 (c) As shown in the photograph, the single crystal prepared in Example 3 is bright and free of impurities. XRD characterization of the single crystal prepared in Example 3 yielded the following results: Figure 6As shown, a comparison with the standard card (ICSD number: 98-016-5226) reveals that all spectral peaks of the single crystal are close to those of Bi₂Se₃ single crystal diffraction peaks, indicating that the prepared single crystal sample and Bi₂Se₃ have similar crystal structures. The elemental content of the single crystal described in Example 2 was analyzed using EDS spectra, and the results are as follows... Figure 7 As shown, characteristic peaks for Bi, Sb, Te, and Se appear, with the elemental composition ratio approaching 1:1:1:2. Due to the low Sn content, characteristic Sn peaks cannot be observed in the EDS spectrum. However, Sn doping can be indirectly indicated by comparing the resistivity and mobility of doped and undoped samples. Furthermore, the EDS results between selected regions show minimal difference, indicating excellent crystal homogeneity.

[0037] The electrical properties of the single crystal prepared in Example 3 were tested at a temperature of T=2K. Electron transport measurements revealed a surface state electron mobility as high as 6900 cm⁻¹. 2 / Vs, such as Figure 11 As shown, the ultra-high electron mobility indicates high crystal quality.

[0038] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.

Claims

1. A bulk insulating topological insulator single crystal with ultra-high electron mobility, characterized in that: The chemical formula of the single crystal is Sn. x Bi 1-x SbTeSe2, where 0.02≤x≤0.04; The single-crystal material is prepared by the following method, the steps of which include: (1) The oxide layer on the surface of Sn particles, Bi particles, Sb particles, Te particles and Se particles is removed by hydrogen reduction method; (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn, Bi, Sb, Te and Se in step (1) to remove the oxide layer on the surface in a glove box with water and oxygen content less than 0.1 ppm and filled with argon gas. Place the weighed raw materials in a quartz tube with a conical bottom and vacuum seal the quartz tube. (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, heat it to 850℃~900℃, keep it at a constant temperature for 48h~72h and shake it, then cool it down to 500℃~550℃, keep it at a constant temperature for more than 24h, and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgeman furnace. Set the temperature of the central area of ​​the Bridgeman furnace to 750℃~720℃. The conical bottom of the quartz tube containing the precursor descends through the central area of ​​the Bridgeman furnace at a speed of 0.5mm / h~2mm / h until the bottom of the furnace. Then close the Bridgeman furnace. (5) Open the quartz tube, take out the crystal, and obtain a bulk insulating topological insulator single crystal with ultra-high electron mobility.

2. A method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in claim 1, characterized in that: The method steps include: (1) The oxide layer on the surface of Sn particles, Bi particles, Sb particles, Te particles and Se particles is removed by hydrogen reduction method; (2) According to the stoichiometric ratio of the topological insulator single crystal, weigh the raw materials Sn, Bi, Sb, Te and Se in step (1) to remove the oxide layer on the surface in a glove box with water and oxygen content less than 0.1 ppm and filled with argon gas. Place the weighed raw materials in a quartz tube with a conical bottom and vacuum seal the quartz tube. (3) Place the quartz tube after vacuum sealing in step (2) into a high-temperature furnace, raise the temperature to 850℃~900℃ after 11h~12h, keep the temperature constant for 48h~72h and shake it 30~40 times, then cool it down to 500℃~550℃ at a rate of 3℃ / h~5℃ / h, keep it at the temperature for more than 24h, and then close the high-temperature furnace to obtain the precursor. (4) Place the quartz tube after heat preservation in step (3) into a vertical Bridgeman furnace. Set the temperature of the central area of ​​the Bridgeman furnace to 750℃~720℃. The conical bottom of the quartz tube containing the precursor descends through the central area of ​​the Bridgeman furnace at a speed of 0.5mm / h~2mm / h until the bottom of the furnace. Then close the Bridgeman furnace. (5) Open the quartz tube, take out the crystal, and obtain a bulk insulating topological insulator single crystal with ultra-high electron mobility.

3. The method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in claim 2, characterized in that: In step (1), Sn particles, Bi particles, Sb particles, Te particles and Se particles are respectively loaded into a quartz tube, and then purged with argon in a vacuum sealing system. Finally, hydrogen gas at a pressure of more than 0.8 atmospheres is introduced into the quartz tube to seal the hydrogen gas inside the quartz tube. The above raw materials are annealed at a temperature 50°C below their respective melting points to remove the oxide layer on the surface. After annealing, a diamond cutter is used to cut a groove around the sealed quartz tube. The sealed quartz tube is then broken open in a glove box filled with argon gas and with a water and oxygen content of less than 0.1 ppm to obtain raw materials Sn, Bi, Sb, Te and Se with the oxide layer removed.

4. The method for preparing a bulk insulating topological insulator single crystal with ultra-high electron mobility as described in claim 2, characterized in that: In step (2), the quartz tube is placed under a vacuum of less than or equal to 5 × 10⁻⁶. -4 The Pa sealing system is sealed.